A flow-cytometric method for the separation and quantitation of normal and apoptotic thymocytes - Sun, X M; Snowden, R T; Skilleter, D N; Dinsdale, D; Ormerod, M G; Cohen, G M (Analytical biochemistry, 1992)
Using flow cytometry, we describe a method for separating and quantifying normal and apoptotic thymocytes. Apoptosis was induced in isolated thymocytes from immature rats by treatment with the glucocorticoid dexamethasone or the antitumor agent etoposide. Subsequent incubation with the vital bisbenzimidazole dye Hoechst 33342 and the DNA intercalating agent propidium iodide enabled three distinct populations of cells to be identified and sorted by flow cytometry. Dead cells fluoresced red due to propidium iodide whereas normal and apoptotic cells fluoresced blue due to Hoechst 33342. Apoptotic cells were distinguished from normal thymocytes both by their higher intensity of blue fluorescence and by their smaller size as determined by a reduction in forward light scatter. The larger cells, with low blue fluorescence, showed normal thymocyte morphology by electron microscopy and the absence of any DNA fragmentation as measured by agarose gel electrophoresis. In contrast, the smaller cells showed both the morphological characteristics of apoptosis and extensive internucleosomal fragmentation of DNA to multiples of approximately 180 bp. Using this method, a time-dependent induction of apoptosis by dexamethasone, which was inhibited by cycloheximide, actinomycin D, and aurin tricarboxylate, was observed. The method should facilitate mechanistic studies on the induction of apoptosis in thymocytes.